Inspiring student writers : strategies and examples for teachers - Scheft, Tom (Language, literacy, and learning., 2009)
Getting our students to write and write well is a process Tom Scheft explains and explores, offering practical and theoretical guidance, while providing uplifting, thought provoking examples of a writing assignment for students middle grades through master's level. An invaluable supplemental text for teacher education programs and in-service programs, Scheft mines his experience working with student writers in public schools and universities. He also covers: the research-backed case for autobiographical, reflective writing helping student writers understand and deal with rejection honest, practical strategies for dealing with dialect differences. Professors, English teachers, and students: This book will help enhance writing through time-tested, user-friendly strategies and powerful examples.